Improving the Effect of Work Satisfaction on Job Performance through Employee Engagement - Zainal Arifin; Nazief Nirwanto; Abdul Manan (International Journal of Multi Discipline Science, 2019)
The purpose of this study to examine the effectiveness of employee engagement increases the effect of job satisfaction on job performance. This research is quantitative causality using a survey method that examines the relationship and influence between variables of research by analyzing 138 workers any mining companies that most cannot meet production targets in Kalimantan. The findings revealed that absorption full mediated the relationship between job satisfaction and job performance Management must invite employees to formulate job satisfaction, pay attention to employee conditions, selectively select employees, provide training to increase employee engagement. This paper is the first one to examine how employee engagement can function to mediate the relationship between job satisfaction and job performance.